Phlorizin Protects Against Oxidative Stress and Inflammation in Age-Related Macular Degeneration Model - Zhen-Yu Liao; Chih-Yu Hung; Yu-Jou Hsu; I-Chia Liang; Yi-Chun Chen; Chao-Hsien Sung; Chi-Feng Hung (Biomolecules)
Background:Sweet Tea (Lithocarpus polystachyus Rehd.), a traditional ethnobotanical medicine, contains phlorizin, a dihydrochalcone compound with antioxidative and anti-inflammatory properties. Given the critical role of oxidative stress and inflammation in age-related macular degeneration (AMD), this study tested the hypothesis that phlorizin mitigates oxidative damage and inflammation in AMD models, thereby offering therapeutic potential. Materials and Methods: Adult retinal pigmented epithelial cells (ARPE-19) were pre-treated with phlorizin (0.01–0.1 μM) and subjected to oxidative stress induced by ultraviolet A (UVA) radiation or sodium iodate (NaIO3). Cell viability, reactive oxygen species (ROS) production, MAPK/NF-κB signaling, and the level of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and pro-angiogenic factors (VEGF, MMP2, MMP9) expression were assessed using MTT assays, fluorescence imaging, Western blotting, and RT-qPCR. In vivo, a laser-induced choroidal neovascularization (CNV) mouse model was used to evaluate phlorizin’s effects on CNV formation and vascular leakage via fundus photography and fluorescence angiography. Result: Phlorizin significantly enhanced cell viability, reduced ROS production, inhibited MAPK/NF-κB activation, and downregulated inflammatory and angiogenic mediators. In vivo studies confirmed the reduced CNV formation and vascular leakage following the phlorizin treatment. Conclusions: Phlorizin demonstrated significant protective effects against oxidative stress and inflammation, highlighting its therapeutic potential for treating AMD.